1994
DOI: 10.1002/syn.890180407
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in TRH receptors in temporal lobe of schizophrenics: A quantitative autoradiographic study

Abstract: We utilized quantitative autoradiography to determine the distribution of receptors for thyrotropin-releasing hormone (TRH) throughout the human temporal lobe and to examine the distribution of these receptors in discrete subregions of the temporal lobe from patients diagnosed premortem with schizophrenia. When compared to non-neurologic controls, schizophrenic patients demonstrated an increase of 51% in the concentration of TRH receptors in the molecular layer of the dentate gyrus. Within nuclei of the schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Moreover, physiological neuronal population events, as well as abnormal neuronal activity during temporal lobe seizures recorded in the amygdala have been found to precede corresponding events in the hippocampus (Paré et al, 1995;Gotman and Levtova, 1996). Clinically, both imaging (Shenton et al, 1992;Bogerts et al, 1993;Marsh et al, 1994;Lawrie and Abukmeil, 1998) and postmortem (Bogerts et al, 1985;Reynolds et al, 1990;Okada et al, 1991;Lexow et al, 1994) studies have consistently demonstrated concordant changes in both the amygdala and the hippocampus in SZ. Taken together, these observations support the hypothesis that the amygdala could be involved in the induction of hippocampal abnormalities found in SZ brain.…”
mentioning
confidence: 91%
“…Moreover, physiological neuronal population events, as well as abnormal neuronal activity during temporal lobe seizures recorded in the amygdala have been found to precede corresponding events in the hippocampus (Paré et al, 1995;Gotman and Levtova, 1996). Clinically, both imaging (Shenton et al, 1992;Bogerts et al, 1993;Marsh et al, 1994;Lawrie and Abukmeil, 1998) and postmortem (Bogerts et al, 1985;Reynolds et al, 1990;Okada et al, 1991;Lexow et al, 1994) studies have consistently demonstrated concordant changes in both the amygdala and the hippocampus in SZ. Taken together, these observations support the hypothesis that the amygdala could be involved in the induction of hippocampal abnormalities found in SZ brain.…”
mentioning
confidence: 91%
“…TRH concentration was decreased in the AD hippocampus compared to normal elderly controls (Luo et al, 2002). However, no significant differences from non-neuropsychiatric controls were noted on TRH receptor levels within the hippocampus in AD; just a slight alteration was noted in the cortical amygdala in AD (Lexow et al, 1994).…”
Section: Thyrotropin-releasing Hormone Receptorsmentioning
confidence: 72%